ESR investigation of hydrogen and deuterium atoms in impurity-helium solids - Kiselev, S.I.; Khmelenko, V.V.; Bernard, E.P.; Lee, D.M. (Физика низких температур, 2003)
Impurity-helium solids (Im-He solids) are porous solids created by injecting a beam of mixed helium and impurity gases into superfluid ⁴He. In this work we use electron spin resonance (ESR) techniques to investigate Im-He solids containing atoms and molecules of hydrogen and/or deuterium. We have performed studies of low temperature (T ~ 1.35 K) tunnelling chemical reactions in which deuterium atoms replace the hydrogen atoms bound in H₂ or HD molecules to produce large (up to 7.5×10¹⁷cm⁻³) and relatively stable concentrations of free hydrogen atoms. The time dependence of H and D atom concentrations has been investigated for Im-He samples with different initial ratios of hydrogen and deuterium ranging from 1:20 to 1:1.The satellite ESR lines associated with the dipolar coupling of electron spins of H and D atoms to the nuclear moments of the hydrogen nuclei found in neighboring molecules have been observed in Im-He solids. The forbidden hyperfine transition of atomic hydrogen involving the mutual spin flips of electrons and protons has also been observed.